Traumatic mating increases anchorage of mating male and reduces female remating duration and fecundity in a scorpionfly species - Tong, Xin (Proc Biol Sci, 2021)
Traumatic mating is the male wounding his mate during mating using specialized anatomy. However, why males have evolved to injure their mates during mating remains poorly understood. We studied traumatic mating in Dicerapanorpa magna to determine its effects on male and female fitness. The sharp teeth on male gonostyli penetrate the female genitalia and cause copulatory wounds, and the number of scars on the female genitals is positively related to the number of times females mated. When the injurious teeth were encased with low-temperature wax, preventing their penetration of the female's genitalia during mating, male mating success and copulation duration were reduced significantly, indicating the importance of the teeth in allowing the male to secure copulation, remain in copula and effectively inseminate his mate. The remating experiments showed that traumatic mating had little effect on the female mating refractory period, but significantly reduced female remating duration with subsequent males, probably benefiting the first-mating male with longer copulation duration and transferring more sperm into the female's spermatheca. The copulatory wounds reduced female fecundity, but did not accelerate the timing of egg deposition. This is probably the first report that traumatic mating reduces female remating duration through successive remating experiments in animals. Overall, our results provide evidence that traumatic mating in the scorpionfly helps increase the male's anchoring control during mating and provides him advantage in sperm competition, but at the expense of lowering female fecundity.